Open Source Geospatial Solution for Disseminating Green Park Information - Paul, Arati; Mondal, Rabi Sankar; Chakraborty, Debasish (Faculty of Computer Science (FILKOM) Brawijaya University, 2019)
Green parks and open spaces are indispensable parts of an urban environment as they play important roles in promoting public health, protecting natural ecosystems and improving socioeconomic conditions of the city dwellers. Hence, the information of green and open spaces in a city needs to be provided to its governing authority and people for better management and utilisation. WebGIS technology is capable of maintaining and disseminating green park information among its users over the web. The availability of open source geospatial software and tools made this technology more cost effective and acceptable to the user community. In present study an interactive and user friendly WebGIS enabled solution is developed for green parks of Kolkata city that facilitates city dwellers and decision makers to search and visualise green parks both on map and satellite image along with park information and ground photo. It is an easy deployable solution that helps in urban planning for creating new as well as preserving the existing green spaces.